مساهمة شبكات التواصل الإجتماعي في تطوير سلوك المستهلك - روان سلماوي; خلود فقير (My University, 2021)
The study that was discussed aims to address determining the extent to which social networks contribute to the development of consumer behavior by conducting a field study on a sample of second-year master students who use social networks at the University of Mohamed Sherif Mosadeya in the state of Souk Ahras, where the study sample included 348 items The study followed the descriptive analytical approach to test the hypotheses and relied on the paper questionnaire technique. The studyproducedseveralfindings, the most important of whichwas the extent to which social media networks contributed to the development of consumer behaviour. How to feed social networks with links to networking sites and online tools, whichenableconsumers to obtainreliable information about the services and productstheyseek ................................................. تهدف الدراسة التي تم التطرق إليها إلى معالجة تحديد مدى مساهمة شبكات التواصل الاجتتااي ي ططوير سووك الدستهو م خلال القيام بدراسة ميدانية يوى يينة م طوبة السنة ثانية ماستر م مستعاو شبكات التواصل الاجتتااي بجامعة محاد شريف مسايدية ي ولاية سوق أهراس حيث اشتاوت يينة الدراسة يوى 348مفردة ، اطبعت الدراسة الدنهج الوصف التحويو لاختبار الفرضيات وتم الايتااد فيها يوى طقنية الاستبيان الورق . طوصوت الدراسة إلى يدة نتائج أهمها مدى مساهمة شبكات التواصل الاجتتااي ي ططوير سووك الدستهو ، وختات الدراسة بعدة طوصيات منها، كيفية طغذية شبكات التواصل الاجتتااي بروابط تمك م الربط بين مواقع التواصل و الأدوات الالكترونية،التي تمك الدستهو م الحصول يوى معوومات موثوقة ي الخدمات و الدنتجات التي يبحث ينها.